Dunaiser City in the Islamic Period (534–136A.H/1139-1335A.D) Culture and Political Research - Hassan, Darwish Y. (Humanities Journal of University of Zakho, 2017)
This study deals with history of one of Kurdish cities in turkeys Kurdistan named ((Dunaiser)) in Islamic period, ((Koj Hisar)) in ottoman period and ((Kizil Tepe)) in contemporary Turkey. The study examines its history between the years (534–136A.H/1139-1335A.D). The study consists of three topics. The first one deals with its name ((Dunaiser)), its geographical location and the beginning of its emergence. The second topic tackled the history of ((Dunaiser)) since Islamic conquest briefly, then its history during the rule of Mardin Artuqids, until the end of Ilkanid rule in Diyar Bekir region. The third topic examines the administrative and scientific aspects of ((Dunaiser)) city.